QUALITATIVE RELATIONSHIPS OF WATER MIGRATION IN HIGHWAY EMBANKMENT CLAY SOILS (Academic journal Industrial Machine Building Civil Engineering, 2017)
The influence on highway embankment clay soil continuous strength some factors:  soil skeleton density after it’s compaction in the embankment, embankment height, time factor (the number of days that embankment «rests» before it’s service is analyzed. The methodology of physical water migration modeling by the highway embankment height through time changes research of clay loam moisture, placed in plastic tubes and compacted at water saturation factor Sr = 0,85 to soil skeleton density rd = 1,50 − 1,65 g/cm3 is developed and realized. The moisture changes graphs of light silt loam at soil skeleton density for the tubes height for each given soil skeleton density and for each accepted time-lagged is plotting in the article. New experimental relationships of compacted highway embankment clay loam moisture conditions and it’s time-lagged till service start, which it’s expedient to consider at optimal clay soils compaction criteria improving, which provide highway embankment long-term strength are established.